Researching Binge-Watching. (September 2020) - Jenner, Mareike
This piece gives an overview of the different ways binge-watching is explored and analysed in contemporary television studies. It specifically explores the way binge-watching has been covered in the technological histories of television, fan studies, audience reception research, and narratology. In this, it insists that binge-watching is deployed in different ways within the broad and diverse field of television studies. The distinct uses of binge-watching in different sub-fields of television studies makes it a term that can be deployed in a variety of ways, suggesting that there can be no 'one' definition, also allowing for its resilience in the face of constant change of the medium.